2013
DOI: 10.3329/pa.v22i1-2.16470
|View full text |Cite
|
Sign up to set email alerts
|

Does Feeding System Influence Parasitism in Black Bengal Goats in Bangladesh?

Abstract: To study the parasitism in goats in relation to different feeding systems, 1110 goats from different areas of Jaypurhat, Tangail, Netrakona and Mymensingh districts were examined. By fecal sample examination, 76.5% goats were found to be infected with one or more species of endoparasites. In this study, 9 types of helminths' ova were identified such as (3.7%). Two types of protozoa were also detected, namely, Eimeria sp. (7.1%) and Balantidium coli (5.5%). Along with these, five species of ectoparasites were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 11 publications
1
12
0
1
Order By: Relevance
“…Infection of Capillaria spp. in goats was reported from Bangladesh (Rabbi et al, 2011), Thailand (Jittapalapong et al, 2012). However, the prevalence was scanty and as low as less than 2 percent.…”
Section: Capillaria Sppmentioning
confidence: 94%
See 1 more Smart Citation
“…Infection of Capillaria spp. in goats was reported from Bangladesh (Rabbi et al, 2011), Thailand (Jittapalapong et al, 2012). However, the prevalence was scanty and as low as less than 2 percent.…”
Section: Capillaria Sppmentioning
confidence: 94%
“…infection was reported from Bangladesh (Rabbi et al, 2011;Sangma et al, 2012);Nepal (Karki et al, 2012); Nigeria (Amadi et al, 2012;Owhoeli et al, 2013;Usman et al, 2016), Ghana (Futagbi et al, 2015), Ethiopia (Kerie and Seyoum, 2016). The prevalence of infection ranged between 3.2-44.4 percent in goats (Rabbi et al, 2011;Karki et al, 2012;Futagbi et al, 2015). Amadi et al (2012) and Owhoeli et al (2013) from Nigeria reported a prevalence of 6.4-21.1 percent in goats through faecal examination.…”
Section: Schistosomesmentioning
confidence: 98%
“…Another parasite, Capillaria spp. was currently reported to be a prevalence rate (6.98%) that was higher than reported in Italy ( 46 ), Nepal ( 45 ), Bangladesh ( 47 ), and Thailand ( 48 ) (lower than 2%). Capillaria spp.…”
Section: Discussionmentioning
confidence: 71%
“…Kambing yang dipelihara secara semi intensif memiliki resiko lebih tinggi terinfestasi oleh tungau selama penggembalaan sehingga resiko infestasi cestoda juga meningkat. Hal ini sesuai dengan penelitian yang dilakukan Rabbi et al (2011) yang menunjukkan bahwa kambing yang dipelihara dengan penggembalaan lebih banyak terinfestasi oleh tungau dan ektoparasit (59,70%) dibadingkan dengan kambing yang dipelihara secara intensif (8,2%).…”
Section: Materi Dan Metodeunclassified